Clinical care and therapeutic trials in PLS. (2nd November 2020) - Floeter, Mary Kay; Warden, Deborah; Lange, Dale; Wymer, James; Paganoni, Sabrina; Mitsumoto, Hiroshi
Abstract: Primary lateral sclerosis (PLS) is an extremely rare central nervous system degenerative disorder characterized by slowly progressive upper motor neuron loss leading to severe limb and bulbar dysfunction and disability. Although not necessarily life-shortening, PLS disease burden is substantial and improved symptomatic treatments are a major unmet need, especially for the often refractory spasticity that is a core feature of the syndrome. In Section 1, we describe clinical care needs and emphasize a highly personalized approach that can be best attained through multidisciplinary management. In Section 2, we describe progress in clinical trials in PLS that includes advances in symptomatic treatment, disease-modifying therapy, and emerging innovative trials.